MENINGKATKAN KINERJA PROGRAM STUDI DENGAN MENGEMBANGKAN SISTEM MANAJEMEN MUTU ISO 9000: MENGAPA PERLU DAN BAGAIMANA MELAKUKANNYA? - Juliani Dyah Trisnawati; Muhammad Rosiawan (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2002)
In several analysis about the roles and function of a program study in the future that a main roles of education is quality. Program Study that can not keep their quality will be lose in the competition, and make the community not survive in the 21st era.The Program Study has responsibility in quality of realization